2019
DOI: 10.1186/s12882-019-1234-0
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional pruritus assessment in hemodialysis patients

Abstract: BackgroundPruritus is a distressing, life-limiting symptom in chronic renal failure, affecting 40% of patients. This study aimed to determine uremic pruritus prevalence and investigate the multidimensional impact on hemodialysis patients.MethodsThis descriptive study was performed between March and June 2016. The study included 181 patients undergoing hemodialysis session, who reported pruritus in the prior month. Data were collected using the 5-D Itch Scale, which assesses pruritus based on 5 dimensions, i.e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 30 publications
4
15
0
4
Order By: Relevance
“…Among the included studies, seven were conducted in Mainland China [27][28][29][30][31][32][33], and five each were conducted in Brazil [34][35][36][37][38], Turkey [39][40][41][42][43], and the USA [44][45][46][47][48] (Supplementary Material S3). Nine studies were from the Middle East [49][50][51][52][53][54][55][56][57], and seven were from South Asian countries [58][59][60][61][62][63][64].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the included studies, seven were conducted in Mainland China [27][28][29][30][31][32][33], and five each were conducted in Brazil [34][35][36][37][38], Turkey [39][40][41][42][43], and the USA [44][45][46][47][48] (Supplementary Material S3). Nine studies were from the Middle East [49][50][51][52][53][54][55][56][57], and seven were from South Asian countries [58][59][60][61][62][63][64].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…One study assessed the sources of income [36], and another inquired about subjective perceptions of income level [50]. [75] Details not provided Multiple choices Gerogianni et al, 2018 [76] Multiple choices Perceived levels Hu et al, 2015 [28] Specific ranges Ibrahim and Salamony, 2008 [55] Dichotomized responses Jeon, Kim, and Kim, 2020 [77] Specific ranges Multiple choices [39] Yes/no Employment status was the most frequently used indicator of financial hardship among the included studies (n = 49). It is noteworthy that most of these indicators only reported employment status as a dichotomized variable, such as "employed" or "unemployed" (n = 27).…”
Section: Assessment Of Financial Hardshipmentioning
confidence: 99%
“…The course of itching was “a little bit better, but still present” in 38.7%, while in 5%, it was “getting worse”, as explained by the patients.In 65.2% of cases 6–10 anatomical regions were involved, most commonly over the back followed by upper arm, chest, and abdomen. Palms, soles and face/head had very minimalinvolvement [ 44 ].…”
Section: Clinical Featuresmentioning
confidence: 99%
“… 101 Male sex was also identified as a predictor of pruritus in a study of 6137 patients on hemodialysis across 7 countries, 103 and as an independent risk factor for severe uremic pruritus in prospective studies of 1773 102 and 341 patients on hemodialysis. 100 Other studies defend that female sex predisposes to uremic pruritus, 22 , 104 - 108 but most were limited by small sample size. By contrast, 7 studies concluded that sex does not influence its development.…”
Section: Reviewmentioning
confidence: 99%